Emotional brain. Concepts of history, location and function - Morlán Gracia, Lorenzo (Avances en Supervisión Educativa, 2012)
Doctor Lorenzo Morlán Gracia, Head of the Neurology Department at the Getafe Hospital.First of all a brief historical account of the various theories concerning the functions of the brain is accomplished. It is followed with a comment on several experiments undergone along the 20th century which have highly contributed to the understanding of the emotional brain and the brain mechanisms concerning conduct. Remarkable advances have been made in the understanding of the genetics and neurochemistry of the emotional brain, yet only part of it is known. Knowing the genetic and biochemical profile of human beings will help us understand better their conduct and emotions, their relations to the environment and hence its influences on their behaviour.